Internationalization initiatives and secondary school students' global perspective - MARANA, BRIAN LAWRENCE (Archīum Ateneo, 2017)
This study examines relationships between internationalization initiatives and the three dimensions of global perspective. Participation in four internationalization initiatives are examined: study abroad, the International Baccalaureate Diploma Program, co-curricular activities, and interaction with foreign exchange students. Research subjects were 467 high school students, who took the Global Perspective Inventory (Braskamp et al., 2013) and the Survey of Internationalization Initiatives. Correlation was established using Pearson's r. Respondents were also grouped into levels of high and low participation, and means testing was used to discriminate between scores on the dimensions of global perspective between groups. Participation in all four initiatives was found to correlate with at least one dimension of global perspective. Research implications and implications for schools that employ these initiatives are discussed.